Shear exfoliation synthesis of large-scale graphene-reinforced nanofibers. (30th September 2020) - Joyner, Jarin; Javvaji, Brahmanandam; Owuor, Peter Samora; Raghavan, Prasanth; Salpekar, Devashish; Tsafack, Thierry; Bhowmick, Sanjit; Vajtai, Robert; Mahapatra, D. Roy; Tiwary, Chandra S.; Ajayan, Pulickel M.
Abstract: Liquid phase exfoliation of two-dimensional (2D) materials from their bulk counterparts has attracted a lot of attention due to its applications in the large-scale synthesis of these materials. Herein, detailed molecular dynamics simulations to understand the exfoliation process of graphene followed by an in-situ exfoliation experiment of graphite suspended in polyacrylonitrile (PAN) using a well-known electro-spinning technique were performed. Submicron-scale fibers reinforced with graphene exhibited multi-fold improvements in terms of mechanical (stiffness, elastic modulus), thermal (degradation temperature) and electrochemical (ionic conductivity) properties. This method is a unique way of synthesizing in-situ composites with large lengths and submicron-diameter fibers. The present technique and the key ideas can be readily extended to other 2D materials as well. Graphical abstract: Image 1